Host‐related factors explaining interindividual variability of carotenoid bioavailability and tissue concentrations in humans. Issue 6 (27th February 2017) - Bohn, Torsten; Desmarchelier, Charles; Dragsted, Lars O.; Nielsen, Charlotte S.; Stahl, Wilhelm; Rühl, Ralph; Keijer, Jaap; Borel, Patrick
Abstract : An overview of factors likely to contribute to interindividual variation of carotenoid bioavailability and thus tissue concentrations is presented. Abstract : Carotenoid dietary intake and their endogenous levels have been associated with a decreased risk of several chronic diseases. There are indications that carotenoid bioavailability depends, in addition to the food matrix, on host factors. These include diseases (e.g. colitis), life‐style habits (e.g. smoking), gender and age, as well as genetic variations including single nucleotide polymorphisms that govern carotenoid metabolism. These are expected to explain interindividual differences that contribute to carotenoid uptake, distribution, metabolism and excretion, and therefore possibly also their association with disease risk. For instance, digestion enzymes fostering micellization (PNLIP, CES), expression of uptake/efflux transporters (SR‐BI, CD36, NPC1L1), cleavage enzymes (BCO1/2), intracellular transporters (FABP2), secretion into chylomicrons (APOB, MTTP), carotenoid metabolism in the blood and liver (LPL, APO C/E, LDLR), and distribution to target tissues such as adipose tissue or macula (GSTP1, StARD3) depend on the activity of these proteins. In addition, human microbiota, e.g. via altering bile‐acid concentrations, may play a role in carotenoid bioavailability. In order to comprehend individual, variable responses to these compounds, an improved knowledge on intra‐/interindividual factors determining carotenoid bioavailability, including tissue distribution, is required. Here, we highlight the current knowledge on factors that may explain such intra‐/interindividual differences.